CFD MODELING OF FUEL DROPLET EVAPORATION AND COMBUSTION PROCESSES IN GDI (GASOLINE DIRECT INJECTION) ENGINES - Mamadaliev Foziljon Abdullaevich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This paper presents a theoretical CFD (Computational Fluid Dynamics) modeling of the evaporation and combustion processes of fuel droplets in GDI-type internal combustion engines. The evaporation and combustion dynamics of the fuel droplet are characterized by spatial and temporal variations of temperature, pressure, and concentration fields. Based on the Navier–Stokes equations and the laws of conservation of mass and energy, a comprehensive mathematical model of the system is developed. Using CFD methods, the temperature and pressure distributions within the combustion chamber were determined. The results demonstrate the physical validity of the model and provide recommendations for optimizing fuel injection parameters to enhance combustion efficiency and reduce emissions.